Forming Future Professional Skills in University - Abbasovna, Atadjanova Shakhnoz (International Journal of Human Computing Studies, 2022)
In modern conditions, the main task of a Pedagogical university is to train a teacher-researcher, a highly professional, spiritual, highly moral personality. A special role in this process is played by updating the content of education and educational technologies. In this article, an attempt is made to see in the French experience important conclusions about the development of future professional skills in students of non-philological universities.